Ninth International Conference on Information Visualisation (IV'05)
DOI: 10.1109/iv.2005.124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect That Touching a Projection Augmented Model Has on Object-Presence

Abstract: A Projection Augmented Model (PA model) is a type of projection based haptic Augmented Reality display. It consists of a real physical model, onto which a computer image is projected to create a realistic looking object. Users can physically touch the surface of a PA model with their bare hands, which has clear experiential value for the types of applications for which they are being developed. However, the majority of PA models are front-projected and do not provide haptic feedback for material properties (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Finally, it is worth highlighting that the results confirm the findings of previous work (Bennett & Stevens, 2005); the majority of participants reported that objectpresence was lower when the Front-Projected ϩ FeelsIncorrect (i.e., simple) PA model was touched, compared to when it was perceived through vision alone (Figure 3). …”
Section: Discussion Of the First Experimentssupporting
confidence: 88%
See 3 more Smart Citations
“…Finally, it is worth highlighting that the results confirm the findings of previous work (Bennett & Stevens, 2005); the majority of participants reported that objectpresence was lower when the Front-Projected ϩ FeelsIncorrect (i.e., simple) PA model was touched, compared to when it was perceived through vision alone (Figure 3). …”
Section: Discussion Of the First Experimentssupporting
confidence: 88%
“…Indeed, previous work has shown that touch is very sensitive for perceiving material properties (see Klatzky & Lederman, 2003 for a review). Previous research supports the prediction that touching a simple PA model reduces object-presence, however, it is not clear from this research why this occurs; that is, the relative contributions of the above mentioned problems are unknown (Bennett & Stevens, 2005).…”
Section: Background: Projection Augmented Modelsmentioning
confidence: 40%
See 2 more Smart Citations
“…Several researchers -Raskar et al [19], Bandyopadhyay et al [1], Raskar and Bimber [18], Bennett and Stevens [2,3] have explored technical challenges associated with the creation of realistic looking objects by projecting computergenerated images on neutral, three-dimensional physical objects.…”
Section: Introductionmentioning
confidence: 99%